2020
DOI: 10.1002/jemt.23502
|View full text |Cite
|
Sign up to set email alerts
|

Comparative foliar anatomical and pollen morphological studies of Acanthaceae using light microscope and scanning electron microscope for effective microteaching in community

Abstract: In this study, foliar anatomy and pollen morphology of 10 species of Acanthaceae has been investigated using light and scanning electron microscopy. The study was aimed to highlight the role of microscopy in microteaching at community for proper characterization of plants using palyno‐anatomical characters including pollen type, exine sculpturing, shape of epidermal cells, pattern of anticlinal wall, type and size of stomata, and trichome. Most of the species have polygonal cell shapes but some species have ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Its allergenic significance is not reported from Pakistan. A detailed study of Acanthaceae pollen can be found in the study by Raza et al (2020).…”
Section: Family: Acanthaceaementioning
confidence: 99%
“…Its allergenic significance is not reported from Pakistan. A detailed study of Acanthaceae pollen can be found in the study by Raza et al (2020).…”
Section: Family: Acanthaceaementioning
confidence: 99%
“…Micromophological characteristics, oil content, FFA content, and biodiesel potential of these nonedible oil yielding seeds have been displayed in Table 1. Whereas, photographs of selected plant species and seeds along with their SEM micrographs have been shown in Figures 1a-d (Ahmad, Samuel, et al, 2011;Gupta, Bhaskar & Andola, 2011;Nabila et al, 2021;Raza et al, 2020;Shah et al, 2013). Classification in the modern synthetic systems and evolutionary study of angiosperm plants relies on ultrastructural and micromophological study of seeds which serves as a valid source of information in this regard (Fatima et al, 2018;Mokbli et al, 2018;Rashid et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A great distinctive variation was observed among these micromophological characteristics, seed sizes, and shapes which can serve as valid pointers for recognition of particular taxa. SEM is one the most dependable and advanced techniques of the present time which can intensely help in resolving various taxonomical issues related to seeds identification and classification (Ahmad, Samuel, et al, 2011; Gupta, Bhaskar & Andola, 2011; Nabila et al, 2021; Raza et al, 2020; Shah et al, 2013). Classification in the modern synthetic systems and evolutionary study of angiosperm plants relies on ultrastructural and micromophological study of seeds which serves as a valid source of information in this regard (Fatima et al, 2018; Mokbli et al, 2018; Rashid et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Just like this research, microscopic techniques using SEM help in studying outer layer of exine and epidermal surfaces in plants (F. Khan et al, 2020;Gul et al, 2019;M. Ahmad, Ozdimir, Zafar, Ahmad, & Sultana, 2019;Mir et al, 2019;Nazish et al, 2020;Noor, Ahmad, Zafar, & Ashraf, 2017;Rahman, Ahmad, Zafar, Mumtaz, & Shah, 2017;Raza et al, 2020;Sadia et al, 2020;Shaheen et al, 2013;Shahzad et al, 2021;Zahra, Ahmad, Shinwari, Zafar, & Sultana, 2014).…”
Section: Fesem Of Mofsmentioning
confidence: 92%